Comparison of eating behaviour by relative weight change status of young adults throughout the COVID-19 pandemic - Seok Tyug Tan; Thivvyatracyny Mohana Kannan (Elsevier, 2023)
Background and purpose: The enforcement of nationwide lockdowns has worsened the obesity epidemic in Malaysia. Therefore, this study aims to compare eating behaviour by relative weight change status among young adults in Malaysia throughout the COVID-19 pandemic. Design/methodology/approach: Socio-demographics, body height, pre-pandemic body weight, and post-lockdown body weight were self-reported by the young adults. The eating behaviour was assessed using the validated Three-Factor Eating Questionnaire-Revised 18-item (TFEQ-R18). The mean difference in eating behaviour subscales was analysed using MANCOVA with a Bonferroni-adjusted post-hoc test. Findings: One-third of the young adults put on body weight due to the lockdowns, with an average relative weight gain of 12.44 ± 9.67%. Conversely, about one-fifth of the young adults reported having lighter body weight in the post-lockdown pandemic phase, with an average relative weight loss of 10.10 ± 4.66%. Young adults in the weight loss category had a significantly higher standardised raw score in cognitive restraints than those in the sustained weight and weight gain categories. In addition, young adults in the weight gain category had statistically higher standardised raw scores in uncontrolled eating and emotional eating compared to those in the sustained weight category. Weight trajectory during the COVID-19 pandemic is linked to disordered eating behaviour among young adults in Malaysia. Originality/value: The findings presented in this study can be potentially valuable in formulating weight management strategies in the post-COVID-19 era.